Optimalisasi Pemantauan Pertumbuhan dan Perkembangan Balita untuk Mencegah Stunting - Lulu Antasari; Tiara Pratiwi; Sonia Renata Reva; Monica Setyowati; Dhita Widya Ananta; Liss Dyah Dewi Arini (STIKes Ibnu Sina Ajibarang, 2025)
Stunting is a significant public health problem, especially in developing countries, which can hinder children's growth and development. Optimizing monitoring of the growth and development of toddlers is a crucial step in preventing stunting. This research aims to evaluate the effectiveness of existing monitoring methods and develop data-based strategies to detect growth problems early. Using quantitative and qualitative approaches, this research collects data from health facilities, families and communities on growth indicators, eating patterns and socio-economic factors. The results show that routine and integrated monitoring with parental education regarding nutrition and health can increase family awareness and participation in efforts to prevent stunting. These recommendations include developing more efficient information systems, increasing access to health services, as well as public awareness campaigns to support optimal growth of toddlers. Thus, it is hoped that optimizing monitoring of the growth and development of toddlers can become an integral part of national efforts to tackle the problem of stunting.